Dynamic organizational learning: a narrative inquiry into the story of Huawei in China. Issue 4 (8th August 2017) - Chang, Li-Chung; Ho, Wei-Ling; Tsai, Sang-Bing; Chen, Quan; Wu, Chi-Cheng
Abstract: In this paper, we apply a model derived from dynamic capability theory to analyse the evolution and development of Huawei as an emerging MNC that is also a dynamic learning organization. We show how this firm has evolved through four distinct eras, characterized in succession by imitation, improvement, integration and cross-disciplinary engagement. Each era has involved a sequence of steps, beginning with opportunities, and followed by path, position, processes and transformation. Through much of its history, Huawei drew heavily on outside expertise. By contrast, the contemporary Huawei has become self-sufficient, as progressive transformations have enabled the firm to acquire dynamic capability for developing unique client-driven solutions by combining knowledge from diverse internal expert communities.